Health care strategy for ensuring work ability in an aging Korea. Issue 1 (December 2016) - Park, Jungsun; Park, Jong-tae; Kim, Soo; Yoo, Cheol-In; Son, Junseok; Yim, Jun; Kim, Dae-seong; Rhee, Kyung; Kim, Yangho
Abstract The rapid aging trend in South Korea will cause a growing shortage of labor and decreasing quality of the labor force. The purpose of this commentary is to recommend a health care strategy to maintain and promote the work ability of employees in an aging Korea. Strategies to promote the work ability require the collaboration of governmental agencies at the central and local levels. First, the common goal should be the reinforcement of follow-up measure in general medical examinations and the promotion of healthy lifestyles for workers. Second, collaborating activities should be performed among the Worker's Health Center, the Health Promotion Center, and community health centers. In conclusion, health care strategies for ensuring the work ability in an aging Korea require the collaboration of governmental agencies at the central and local levels.